Lentil and Fava Bean With Contrasting Germination Kinetics: A Focus on Digestion of Proteins and Bioactivity of Resistant Peptides - Bautista-Expósito, Sara; Vandenberg, Albert; Peñas, Elena; Frias, Juana; Martínez-Villaluenga, Cristina (Frontiers in Plant Science, 2021)
Germination offers advantages to improve legume protein digestibility as it disintegrates seed structure and hydrolyzes proteins and anti-nutrients. Seed permeability (related to polyphenol content of seed coats) is an important factor affecting the duration of seed germination and its impact on protein digestibility and bioactivity. The objective was to compare the effect of seed germination on protease activity, structure, and proteolysis of four selected legumes with contrasting seed coat polyphenol profiles (gray zero-tannin lentil [GZL], beluga lentil [BL], and dehulled red lentil [DL]; and zero tannin/low vicine–convicine fava bean [ZF]). Protein hydrolysis was characterized during germination and digestion with respect to proteins, peptides, and free amino acids (FAAs). In vitro antihypertensive and antioxidant activities of digests were investigated, and the peptidomic characterization [high-performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS)] and identification of bioactive fragments in intestinal digests were performed. Regardless of the seed type, germination increased protease activity and reduced the levels of phytic acid, trypsin inhibitors, and tannins (only in BL). A significant proteolysis of the 7S and 11S globulins and a concomitant increase of peptides and FAAs were observed in all sprouted legumes. Digestion kinetics in sprouts revealed a faster generation of FAAs and peptides than in dry seeds, with changes being more evident for DL, associated with a faster imbibition, germination, and sprout growth. In contrast, BL sprouts showed the lowest protein digestibility, likely due to a lower protease activity, seed structure disintegration, and higher anti-nutrient levels in comparison to GZL, DL, and ZF. Moreover, the digestion of sprouts resulted in a higher number of resistant peptides in DL and ZF that matched with previously reported bioactive sequences, suggesting a promising health potential of legume sprouts that was confirmed in vitro. The results suggested that the germination process improved protein digestibility and the health-promoting potential of lentil and fava bean proteins although these changes were more evident in DL due to its rapid imbibition, faster germination, and sprout development. This study will provide important information for either plant breeders to develop legume varieties with permeable seed coats or food producers that could use dehulled seeds for efficient production of sprouts as sustainable food sources of plant proteins with improved nutritional and healthy properties.